Evaluasi Penerapan Electronic Court (e-Court) menggunakan Kerangka Kerja Human, Organization, dan Technology (HOT-FIT) di Pengadilan Agama Jayapura Papua - Adinda Paraswika Fabanyo; Ismiarta Aknuranda; Bondan Sapta Prakoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Web-based Electronic Court (e-Court) is an information system provided to assist court employees in the process of registration of cases and trials in court. However, there are some problems in the application of e-Court such as frequent disruptions on the server as well as difficulty for elderly employees in using the e-Court system. In addition, during the implementation of e-Court has never been evaluated by looking at the influence factors of users, technology and organization. Thus, it is necessary to evaluate in order to achieve maximum service. This study aims to describe the success in the application of e-Court using the Human, Organization, and Technology (HOT-Fit) Model framework. Researchers apply quantitative approaches that make questionnaire results as the main research data as well as qualitative approaches derived from data obtained through interviews as complementary data in this study that is useful to strengthen the results of quantitative methods. Interviews are used to strengthen the results of quantitative questionnaires. The data collected quantitatively is processed by applying descriptive statistics. The results of this study show that the application of variables in HOT-fit to e-Court is good. However, there are still some users who find it difficult and the e-Court system is still not good.